2017
DOI: 10.3389/fpls.2016.01977
|View full text |Cite
|
Sign up to set email alerts
|

Intron-Mediated Enhancement: A Tool for Heterologous Gene Expression in Plants?

Abstract: Many plant promoters were characterized and used for transgene expression in plants. Even though these promoters drive high levels of transgene expression in plants, the expression patterns are rarely constitutive but restricted to some tissues and developmental stages. In terms of crop improvement not only the enhancement of expression per se but, in particular, tissue-specific and spatial expression of genes plays an important role. Introns were used to boost expression in transgenic plants in the field of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 131 publications
(258 reference statements)
3
72
0
2
Order By: Relevance
“…Intron position is important for many transcripts. While most introns are located within the CDS (coding sequence of the main open reading frame, mORF), it is well established that some specific introns in the mRNA leader (5′ untranslated regions, 5′UTRs) enhance gene expression in animals and plants ( 4 , 8 , 9 ). For example, the maize Ubi1 intron enhances expression ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intron position is important for many transcripts. While most introns are located within the CDS (coding sequence of the main open reading frame, mORF), it is well established that some specific introns in the mRNA leader (5′ untranslated regions, 5′UTRs) enhance gene expression in animals and plants ( 4 , 8 , 9 ). For example, the maize Ubi1 intron enhances expression ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since SE bound preferentially to ILGs, we investigated the characteristics of intronless versus intron-rich genes. Intron splicing offers opportunities for the regulation of gene expression at various levels; introns positively influence transcription, RNA stability, and translation in a process known as ‘intron-mediated enhancement of gene expression’ ( Laxa, 2016 ). In agreement with the finding that introns positively affect gene expression, we found that Arabidopsis genes with no or few introns exhibited lower maximum expression levels across a wide range of developmental stages and stress responses compared to intron-rich genes ( Figure 2—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, while the 35S:TERT construct lacks introns, the ACT2:TERT construct contains an intron in the 5´UTR. It is well established that presence of introns enhances transgene expression in plants (Laxa, 2016), and therefore, the intronless 35S:TERT construct may produce a suboptimal amount of TERT. Alternatively, the 35S promoter may not be efficiently active in tissues where telomerase is most needed, such as rapidly growing embryos (Sunilkumar, Mohr et al, 2002).…”
Section: Discussionmentioning
confidence: 99%